2022
DOI: 10.1002/mabi.202200425
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Forming Norbornene‐Tetrazine Hydrogels with Independently Tunable Properties

Abstract: Although photopolymerization reactions are commonly used to form hydrogels, these strategies rely on light and may not be suitable for delivering therapeutics in a minimally invasive manner. Here, hyaluronic acid (HA) macromers are modified with norbornene (Nor) or tetrazine (Tet) and upon mixing click into covalently crosslinked Nor-Tet hydrogels via a Diels-Alder reaction. By incorporating a high degree of Nor and Tet substitution, Nor-Tet hydrogels with a broad range in elastic moduli (5 to 30 kPa) and fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…61 Norbornene−tetrazine coupling of HA-modified gels using IEDDA chemistry has also been explored. 62 Gultian et al separately modified the carboxyl groups in HA with 5norbornene-2-methylamine and tetrazine-amine for subsequent cross-linking in PBS at 37 °C (Figure 1E). 62 Tetrazine tends to degrade in aqueous environments due to nucleophilic attack of its nitrogen atoms by water molecules.…”
Section: Hydrogels For Local Delivery Of Therapeutic Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Norbornene−tetrazine coupling of HA-modified gels using IEDDA chemistry has also been explored. 62 Gultian et al separately modified the carboxyl groups in HA with 5norbornene-2-methylamine and tetrazine-amine for subsequent cross-linking in PBS at 37 °C (Figure 1E). 62 Tetrazine tends to degrade in aqueous environments due to nucleophilic attack of its nitrogen atoms by water molecules.…”
Section: Hydrogels For Local Delivery Of Therapeutic Proteinsmentioning
confidence: 99%
“…62 Gultian et al separately modified the carboxyl groups in HA with 5norbornene-2-methylamine and tetrazine-amine for subsequent cross-linking in PBS at 37 °C (Figure 1E). 62 Tetrazine tends to degrade in aqueous environments due to nucleophilic attack of its nitrogen atoms by water molecules. Methylphenyltetrazine substitution offers greater stability than tetrazine substitution due to resonance stabilizing effects of the aromatic ring, which reduces its level of degradation while still maintaining reactivity.…”
Section: Hydrogels For Local Delivery Of Therapeutic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the specificity of the tetrazinenorbornene reaction facilitated the sequential modification of the network via thiol-ene photochemistry. The accessibility of the tetrazine molecule in comparison to other bioorthogonal click reagents was subsequently investigated as a new tool for developing cell-instructive hydrogels of all kinds (i.e., alginates, [153] hyaluronic acids (HA), [154] and gelatins [155] ), etc. for tissue engineering applications (Scheme 10).…”
Section: Photochemical 2d and 3d Printing For Precision Tissue And Ma...mentioning
confidence: 99%
“…22,26 Our group recently developed injectable hydrogels based on a Diels Alder reaction between norbornene and tetrazine modified hyaluronic acid macromers. 27 These hydrogels can be used to inject cells through clinically used syringe needles without impacting viability, and peptides can be covalently bound to the hydrogel backbone without altering mechanical properties. Using this platform, we synthesized DWIVA-functionalized injectable hydrogels and found that encapsulated human mesenchymal stem cells (MSCs) exhibited increased alkaline phosphatase (ALP) expression in vitro, and acellular injections induced local mineralized bone formation in vivo after 4 weeks.…”
mentioning
confidence: 99%